THE FORMS OF KINSHIP TERM IN MINANGKABAULANGUAGE USED BY NAGARI SIMAWANG SOCIETY - Denil, Mauli (TELL - US JOURNAL, 2019)
This article aims to describe the forms of kinship term in Minangkabau language used by society in NagariSimawang. The data are collected by using questionnaire, interview, cross check, elicitation, recording, and note taking. In addition, non-participant observation is also used to collect the data of using address terms in a conversation. In analyzing the data, content analysis method is used by sorting and classifying data based on the type or category of address terms theory through the systems of kinship relation in Minangkabau culture. The results of analysisshow the characteristic of Minangkabau culture in using address term such as a form of kinship term, kinship terms which are added by pronouns and adjectivc, and also titles only. Keywords:address term, kinship term, minangkabau language, kinship system in minangkabau culture